When rebels govern oil. (December 2022) - Ahram, Ariel I.
Highlights: Rebel groups are increasingly involved in managing and selling oil internationally. Rebels have set up alternative institutions for managing oil, including national oil companies. Rebel oil can affect the course of conflict and global oil markets. Abstract: Numerous oil and gas-producing countries have suffered civil war and internal conflict in the last two decades. Such political instability has had significant ramifications for global energy security. The literature addressing the connection between oil production and civil wars focuses on the contest for physical control over fields, pipelines, transport hubs, and other physical infrastructure. This overlooks how rebels make symbolic and legal claims to oil ownership that parallel the physical confrontation. Alternative national oil companies and other quasi-legal entities assert rebels' authority to manage and dispose of oil. Here, I typologize different forms of rebel oil government and offer empirical examples of each form. I show that rebel oil governance can affect the course of conflicts, helping rebels substantiate internal control and entice international backers. More broadly, these quasi-legal rebel entities disrupt and realign global energy supplies.